2014
DOI: 10.1292/jvms.13-0202
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of L-Carnitine on Oxidative Stress Responses of Experimental Contrast-Induced Nephropathy in Rats

Abstract: This study was conducted to investigate the prophylactic effects of carnitine against contrast-induced nephropathy (CIN) and its relation to oxidant/antioxidant status in kidney, liver, heart, spleen and lung tissues in a CIN rat model. Twenty-eight adult male Wistar rats were divided into 4 groups, the control, contrast media (CM), carnitine and contrast media+carnitine (CM+carnitine) groups. Animals were placed in individual metabolism cages, and on the 2nd day, rats were deprived of water for 24 hr. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 54 publications
6
34
0
Order By: Relevance
“…Treatment of carnitine significantly reduced MDA and activate the antioxidant status which consistent with Boyacioglu et al, (2014) who stated that renal and serum MDA decreased and GSH increased after carnitine treatment in contrast mediainduced acute renal insufficiency. It has been suggested that improved GSH levels after L-carnitine addition in rats may also be attributed to increased nicotinamide adenine dinucleotide phosphate hydrogen (NADPH) generation through increased fatty acid metabolism (Thangasamy et al .,2009).…”
Section: Discussionsupporting
confidence: 87%
“…Treatment of carnitine significantly reduced MDA and activate the antioxidant status which consistent with Boyacioglu et al, (2014) who stated that renal and serum MDA decreased and GSH increased after carnitine treatment in contrast mediainduced acute renal insufficiency. It has been suggested that improved GSH levels after L-carnitine addition in rats may also be attributed to increased nicotinamide adenine dinucleotide phosphate hydrogen (NADPH) generation through increased fatty acid metabolism (Thangasamy et al .,2009).…”
Section: Discussionsupporting
confidence: 87%
“…Many disease-related renal fibroblasts originate from transdifferentiated tubular epithelia cells at the sites of injury [18], and L-carnitine has been studied for its protective effects against renal oxidative injury and fibrotic process [13,19], so we set out to determine whether L-carnitine could alleviate COM-induced cell dedifferentiation.…”
Section: L-carnitine Protects Mdck Cells From Com-induced Dedifferentmentioning
confidence: 99%
“…and multiple organ damage by the contrast agent. 28 Our research also manifested that the LC reduced eryptosis by inhibiting oxidative stress. It is necessary to probe the best concentration and effective acting time.…”
Section: Discussionmentioning
confidence: 54%